The tragic representation of the armed struggle in Palavras cruzadas by Guiomar de Grammont - Burianová, Zuzana (Romanica Olomucensia, 2020)
This paper deals with the role of the tragic in the novel Palavras cruzadas (2015) by the Brazilian writer and historian Guiomar de Grammont. The goal is to analyse how Grammont's novel portrays the Araguaia Guerrilla War, as well as the whole armed struggle against the military dictatorship in Brazil. Starting from the argument that the tragic, though no longer associated only with dramatic representation, remains present in modern literature, the paper first analyses the inspiration Grammont's novel draws from ancient tragedy. The tragic dimension of the narrative is then discussed in relation to the debate over the significance of the armed resistance and to the issue of forced disappearances during the Brazilian dictatorship. Though criticized for presenting a conciliatory view of the dictatorial past, the novel expresses a clear denunciation of the military regime. However, at the same time it points to the contradictions of the armed struggle, as it unveils the tragic trajectory of a couple of young militants who participated in the Araguaia Guerrilla War. Grammont's representation of the armed struggle is based mainly on the experiences of the families of the victims of political repression. It demonstrates that they must deal not only with a traumatic loss, but also with a prolonged silence about the past on the part of the Brazilian authorities. The novel seeks, through its protagonist who tries to resist this silence, a way to overcome the trauma, if only on a personal level.
Keywords: Brazilian military dictatorship; Araguaia Guerrilla War; forced disappearance; Guiomar de Grammont; novel; tragedy